Development and validation of nomogram to predict overall survival and disease-free survival after surgical resection in elderly patients with hepatocellular carcinoma - Tian, Yuan; Wang, Yaoqun; Wen, Ningyuan; Lin, Yixin; Liu, Geng; Li, Bei (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) is one of the common causes of tumor death in elderly patients. However, there is a lack of individualized prognostic predictors for elderly patients with HCC after surgery.We retrospectively analyzed HCC patients over 65 years old who underwent hepatectomy from 2015 to 2018, and randomly divided them into training cohort and validation cohort in a ratio of 3:1. Univariate Cox regression was used to screen the risk factors related to prognosis. Prognostic variables were further selected by least absolute shrinkage and selection operator regression model (LASSO) and multivariate Cox regression to identify the predictors of overall survival (OS) and disease-free survival (DFS). These indicators were then used to construct a predictive nomogram. The receiver operating characteristic curve (ROC curve), calibration curve, consistency index (C-index) and decision analysis curve (DCA) were used to test the predictive value of these independent prognostic indicators.A total of 188 elderly HCC patients who underwent hepatectomy were enrolled in this study. The independent prognostic indicators of OS included albumin (ALB), cancer embolus, blood loss, viral hepatitis B, total bilirubin (TB), microvascular invasion, overweight, and major resection. The independent prognostic indicators of DFS included major resection, ALB, microvascular invasion, surgical type, blood loss, TB, and pleural effusion. In the training cohort, the ROC curve showed that the predictive values of these indicators for OS and DFS were 0.827 and 0.739, respectively, while in the validation cohort, they were 0.798 and 0.694. The calibration curve nomogram exhibited good prediction for 1-year, 2-year, and 3-year OS and DFS. Moreover, the nomogram models exhibited superior performance compared to the T-staging suggested by C-index and DCA.The nomogram established in this study demonstrate commendable predictive efficacy for OS and DFS in elderly patients with HCC after hepatectomy.